DESAIN ALAT UKUR SUHU DAN KELEMBABAN BERBASIS MIKROKONTROLER ATMEGA 16 - Talapessy, Ronaldo (BAREKENG: Jurnal Ilmu Matematika dan Terapan, 2012)
The has already designed temperature and humidity measurement devices using SHT11 sensor with display results in Liquid Crystal Display (LCD). Manually, the environmenttemperature was measured using a mercury thermometer and the environment humidity was measured by a hygrometer. The results were observed in analog and it often misread thus it caused errors in ready the data. To solve the problem, then were made a design temperature and humidity measuring devices digitally. The processor of this tool is ATMega16microcontroller that processes analog input signals to obtain a digital output. Temperature and humidity sensors SHT11 were used, the measurement results and read digital displayon the LCD. This design produced temperature and humidity measurement, aids accurately, it was ± 0.4 ° C and ± 3%.